Electrodeposited platinum-iridium coating improves in vivo recording performance of chronically implanted microelectrode arrays. (June 2019) - Cassar, Isaac R.; Yu, Chunxiu; Sambangi, Jaydeep; Lee, Curtis D.; Whalen, John J.; Petrossians, Artin; Grill, Warren M.
Abstract: Reliable single unit neuron recordings from chronically implanted microelectrode arrays (MEAs) are essential tools in the field of neural engineering. However, following implantation, MEAs undergo a foreign body response that functionally isolates them from the brain and reduces the useful longevity of the array. We tested a novel electrodeposited platinum-iridium coating (EPIC) on penetrating recording MEAs to determine if it improved recording performance. We chronically implanted the arrays in rats and used electrophysiological and histological measurements to compare quantitatively the single unit recording performance of coated vs. uncoated electrodes over a 12-week period. The coated electrodes had substantially lower impedance at 1 kHz and reduced noise, increased signal-to-noise ratio, and increased number of discernible units per electrode as compared to uncoated electrodes. Post-mortem immunohistochemistry showed no significant differences in the immune response between coated and uncoated electrodes. Overall, the EPIC arrays provided superior recording performance than uncoated arrays, likely due to lower electrode impedance and reduced noise.